Trade and Climate Change: The Challenges Ahead - Nicole A. Mathys; Jaime de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2010)
The outcome of the 15th conference of the Parties to the UNFCC showed a shift from a top-down approach with a collective target favoring environmental objectives to a bottom-up accord favoring political feasibility, with no meaningful binding agreement in sight, as the global climate regime and the global trade policy regime represented by the WTO appear to be on a collision course. Following a review of the alternative architectures for the next Climate Change Agreement, the paper outlines four areas in which trade will play a role: as a purveyor of technological transfer; as a mechanism to separate where abatement takes place from who bears the cost of abatement; as a participation mechanism; and as a way to address the pressures for border adjustments. Political-economy considerations are invoked to predict that a target system with a carbon credit system will be preferable to a carbon tax or to a portfolio system of treaties.
Keywords: F18; Q56; 330; Commerce; Changement Climatique